2022
DOI: 10.3390/nano12132214
|View full text |Cite
|
Sign up to set email alerts
|

Light Scattering and Turbidimetry Techniques for the Characterization of Nanoparticles and Nanostructured Networks

Abstract: Light scattering and turbidimetry techniques are classical tools for characterizing the dynamics and structure of single nanoparticles or nanostructured networks. They work by analyzing, as a function of time (Dynamic Light Scattering, DLS) or angles (Static Light Scattering, SLS), the light scattered by a sample, or measuring, as a function of the wavelength, the intensity scattered over the entire solid angle when the sample is illuminated with white light (Multi Wavelength Turbidimetry, MWT). Light scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Dynamic light scattering (DLS) was also used to determine the size distribution of particle size samples with a submicron scale and provide the surface charge or zeta potential (Zpotential) value of nanoparticles, whereas static light scattering (SLS) or laser diffraction was only utilized to determine the size distribution of nanoparticles with a micron-scale particle size. 35 The results indicated that the particle size of AO-SNPs, as determined by DLS, had an average size of 450 nm (Figure 2a), which is consistent with the FE-SEM result. In contrast, the average particle size of the PDB-SNPs determined by SLS was 0.6 μm (Figure 2b).…”
Section: Biosynthesis and Characterization Of Sulfur Nanoparticlessupporting
confidence: 84%
See 2 more Smart Citations
“…Dynamic light scattering (DLS) was also used to determine the size distribution of particle size samples with a submicron scale and provide the surface charge or zeta potential (Zpotential) value of nanoparticles, whereas static light scattering (SLS) or laser diffraction was only utilized to determine the size distribution of nanoparticles with a micron-scale particle size. 35 The results indicated that the particle size of AO-SNPs, as determined by DLS, had an average size of 450 nm (Figure 2a), which is consistent with the FE-SEM result. In contrast, the average particle size of the PDB-SNPs determined by SLS was 0.6 μm (Figure 2b).…”
Section: Biosynthesis and Characterization Of Sulfur Nanoparticlessupporting
confidence: 84%
“…DLS is preferable for spherical particle size characterization by measuring the hydrodynamic radius. , In contrast to the AO-SNPs, which had a uniform spherical shape, the PDB-SNPs had irregular morphologies; as a result, the hydrodynamic size distribution acquired by using DLS was excessively variable and could not be quantified. However, static light scattering (SLS) is a method for determining the absolute molecular weight by examining the relationship between the light intensity scattered by a particle and its size and molecular weight . The apparent similarity in particle size values between AO-SNPs and PDB-SNPs measured by SLS could be due to their comparable molecular masses rather than size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model is also supported by the fact that both the maximum degree of swelling of this uncross-linked casein fraction and the correlation length of the microstructure is pH-independent, and that both lengths decrease with increasing TGase treatment time. Future use of angle-dependent light scattering, ultra-small angle X-ray scattering as well as high-resolution microscopic techniques also allowing nanomechanical characterisation may help in further determining whether the hypothesis of core-shell assembly of TGase-treated casein microparticles is valid [ 53 , 54 , 55 ]. Furthermore, it should be verified whether during TGase treatment inclusion of non-desirable matter such as TGase itself occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Stokes–Einstein equation defines the relationship between the speed of a particle’s Brownian motion and its hydrodynamic size. Among them, dynamic light scattering (DLS) , is the most widely used method, which records the scattered light fluctuations caused by the Brownian motion of particles. Derivatively, fluorescence correlation spectroscopy measures fluorescence fluctuations to evaluate the HD of fluorescently labeled molecules, and nanoparticle tracking analysis solves HD by tracking and locating scattered light images of minority/single particles to calculate particle diffusion velocity.…”
Section: Introductionmentioning
confidence: 99%